(untitled) - Tanka, Judith (New York, 2014)
The themes are integrated across proficiency levels and the levels are articulated across skill strands. The series combines communicative activities with skill-building exercises to boost students' academic success.
Keywords: English language,Tiếng Anh,Tiếng Anh,English language; Listening,Nói,Nghe,Spoken English